A concepção de mediação de conflitos no ambiente escolar - Eller, Edson Wander (2019)
This study aims to identify the conception of conflict mediation in the school environment. This theme has a relationship with the learning process, in which its field of activity contributes to the development of society and emancipation of individuals through democratic actions. It was investigated the teacher’s performance, as well as his training as a mediator of conflicts in the school environment, deepening a bibliographic and documentary analysis about the project school protection system, SPE, of São Paulo, besides presenting forms of Resolution of these with a view to a dialogical proposal, which takes into account the feelings and views of those involved, as well as promotes the culture of peace. Some practices associated with the culture of peace, called restoratives, provide proactive action procedures that can contribute to an improvement in the prevention and positive resolution of conflicts, contributing to the development of good relations in School environment. We also investigated the analysis of documents pertinent to the subject, how important it is for the teacher to know techniques that, through democratic actions, it becomes possible to perform the mediation of conflicts, to improve the conditions of Relationship between their peers. It was based on authors such as Michael Apple (1997), Álvaro Chrispino (2013), John Dewey (1959), Telma Vinha (2003), among others, as well as an analysis of the document dialogues and mediation of conflicts in schools (2014), which brought significant contribution For the development of this research. The objective was also to analyze how teachers can manage interpersonal conflicts within the teaching institution and how the methodological process of mediation can be perceived by the school team, as well as sensitizing to the use of Simple tools in resources and deep in relationships of coexistence, giving special emphasis to the development of important values, such as respect for social responsibility and protagonism